Prevention of transmission of HIV, hepatitis B virus, hepatitis C virus, and tuberculosis in prisoners. Issue 10049 (10th September 2016) - Kamarulzaman, Adeeba; Reid, Stewart E; Schwitters, Amee; Wiessing, Lucas; El-Bassel, Nabila; Dolan, Kate; Moazen, Babak; Wirtz, Andrea L; Verster, Annette; Altice, Frederick L
Summary: The prevalence of HIV, hepatitis B virus, hepatitis C virus, and tuberculosis are higher in prisons than in the general population in most countries worldwide. Prisons have emerged as a risk environment for these infections to be further concentrated, amplified, and then transmitted to the community after prisoners are released. In the absence of alternatives to incarceration, prisons and detention facilities could be leveraged to promote primary and secondary prevention strategies for these infections to improve prisoners health and reduce risk throughout incarceration and on release. Effective treatment of opioid use disorders with opioid agonist therapies (eg, methadone and buprenorphine) prevents blood-borne infections via reductions in injection in prison and after release. However, large gaps exist in the implementation of these strategies across all regions. Collaboration between the criminal justice and public health systems will be required for successful implementation of these strategies.